TO THE PROBLEM OF THE PERSONAL CREATIVE POTENTIAL DEVELOPMENT - Zavhorodnya, Y. (Continuing Professional Education: Theory and Practice, 2023)
It is proposed the role of higher education in the creative potential formation of the individual. The problems of interpretation definitions of «creativity» in the modern educational space (nature of the appropriate opportunities and cultures that are formed and revealed in the process of training and preparation of its activities in the future, lead to getting productive results in solving non-standard methods of pedagogical influence, through art, reflecting the basis of general and pedagogical culture). Characteristic features of the individual creativity formation and the role of higher education in this process (the foundation of the creative potential of the future teacher are formed are laid during vocational training). It is revealed the necessity of sharing methods for professional development of the individual, and for the creative potential formation of the individual. Based on research by the author proposed to allocate features creative potential (general cultural and professional knowledge, humanitarian ideology on which it is based and regulated activities developed sense of new, high level of creative thinking, its flexibility, not stereotyped and originality, the ability to quickly change methods of action in accordance with the new conditions), provides its definition (dynamic integral formation that defines the human resource development opportunities and its ability to master and implement various productive activities), with the main characteristics of the pedagogical and psychological analysis of this definition.